PENGARUH KEBIJAKAN INSENTIF PAJAK, PELAYANAN FISKUS, DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Prasetyo, Agustinus Andi; Harta Mimba, Ni Putu Sri; Suartana, I Wayan; Nyoman Budiasih, Gusti Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.06.TAHUN.2024, 2024)
This study aims to determine the effect of tax incentive policies, fiscal services, and mandatory awareness on MSME taxpayer compliance during the Covid-19 pandemic. The research design uses quantitative research with a sample of 100 MSMEs. The data analysis technique used regression analysis, determination, significance test with F test and t test. The results of the analysis show that tax incentive policies, tax service services, and taxpayer awareness have a positive impact on MSME taxpayer compliance during the Covid-19 pandemic. The data used is quantitative and the data source used is primary data. The research population is MSME Taxpayers at the Bali Regional Office of the Directorate General of Taxes during 2022, namely 73,014 MSME Taxpayers. The number of samples was determined at 100 MSMEs, determining the number of sample members at each Tax Service Office was carried out using proportional random sampling. The research is only limited to the East Denpasar Primary Tax Service Office and the West Denpasar Primary Tax Service Office, so the research results may also have differences regarding perceptions or interpretations in other places.